Analisis Kebutuhan Pengguna Lulusan Program Studi Perbankan Syariah Di Kabupaten Rejang Lebong - Noprizal Noprizal; Andriko Riko; Khairul Umam Khudhori (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2022)
This study aims to reveal in what positions graduates of the Islamic banking study program are placed. The needs of graduates of the Islamic banking study program are what users want, and where do graduates of the Islamic banking study program work? Until the end of 2018, the Islamic banking study program had completed 542 graduates. This research is field research that uses a qualitative descriptive analysis approach. The subjects of this research are alumni of Islamic banking study programs, both those who work in government, private and entrepreneurial institutions. Alumni users, both from schools and government and private institutions. The determination of research subjects as respondents is by incidental techniques combined with snowball techniques. The research was conducted in the Rejang Lebong Regency. The main data sources are Islamic banking alumni and graduate users. The research succeeded in revealing that (1) Islamic banking graduates work in bank financial institutions, non-banks, and other non-financial economic institutions. (2) The needs of stakeholders for graduates of the Islamic banking study program are still classified as very potential. (3) The position of Islamic banking alumni is still very general, such as administrative staff, cashiers, customer service, tellers, operators, and other temporary employees. It's just that of the many respondents, some have quite prestigious positions, namely lecturers, cooperation and capital analysts, BMT managers, and other positions that are almost similar to him